Respon Pertumbuhan Tanaman Tomat (Solanum lycopersicum) dengan Pemberian Pupuk Hayati Bioneensis dan Pupuk Tunggal N,P,K di Kecamatan Medan Johor - Fadlan Fadlan; Dini Mufriah; Syahriandi Akbari (UNIVERSITAS LABUHANBATU, 2026)
Tomato plants face various challenges, including decreased soil fertility, pest and disease attacks, and the significant impact of climate change on plant productivity. The use of biofertilizers is very relevant to increase tomato growth. The aim of this study was to determine the effect of the dosage of Bioneensis Biofertilizer and Single Fertilizer N, P, K as well as the interaction between the dosage of Bioneensis Biofertilizer and Single Fertilizer NPK on tomato plant growth. This study was conducted on Jl. A.H Nasution, Medan Johor District, Medan City. The research period starts from March to July 2025. This research uses a Factorial Randomized Block Design consisting of 2 factors, namely the first factor is the dose of Bioneensis Biofertilizer (B) where B1 = 10 g / plant, B2 = 20 g / plant, B3 = 30 g / plant, and the second factor is Single Fertilizer N, P, K (P), where P1 = Urea 50 kg / ha (9.6 g / plot), SP36 37.5 kg / ha (7.2 g / plot), KCl 25 kg / ha (4.8 g / plot), P2 = Urea 100 kg / ha (19.24 g / plot), SP36 75 kg / ha (14.44 g / plot), KCl 50 kg / ha (9.6 g / plot), P3 = Urea 200 kg / ha (38.48 g / plot), SP36 150 kg / ha (28.88 g/plot), KCl 100 kg/ha (19.24 g/plot). The results of the study showed that the use of Bioneensis Biofertilizer doses had no significant effect on plant height and number of leaves, with the best treatment being B2 (Bioneensis Biofertilizer 20 g/plant). The use of Single Fertilizer N, P, K (P) had no significant effect on plant height, number of leaves with the best treatment being P2 (Urea 100 kg/ha (19.24 g/plot), SP36 75 kg/ha (14.44 g/plot), KCl 50 kg/ha (9.6 g/plot). The interaction between Bioneensis Biofertilizer (B) and Single Fertilizer N, P, K had no significant effect on plant height, number of leaves with the best treatment being B2P3 Bionensis Biofertilizer 20 g/plant and Single Fertilizer N, P, K.